2011
DOI: 10.4161/psb.6.11.17666
|View full text |Cite
|
Sign up to set email alerts
|

Fearful symmetry in aposematic plants

Abstract: Symmetry has been proposed to increase the efficiency of visual aposematic displays in animals, and I suggest that it may also be true for many aposematic spiny or poisonous plants. For instance, in the very spiny plant taxa cacti, Aloe sp., Agave sp. and Euphorbia sp., which have been proposed to be aposematic because of their colorful spine system, the shoots, and in cacti, the spiny fruits as well, are usually radially symmetric. Moreover, in the radial symmetric shoots of Agave and Aloe their individual sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As part of the study on the evolution of plant protection by spines and thorns conducted in our group (e.g. Lev‐Yadun, 2001, 2003a, b, 2006, 2009a, b, c, 2011; Lev‐Yadun & Ne'eman, 2004, 2006; Halpern et al ., 2007a, b, 2011; Ronel, Malkiel & Lev‐Yadun, 2007; Lev‐Yadun & Gould, 2008; Lev‐Yadun & Halpern, 2008; Lev‐Yadun, Ne'eman & Izhaki, 2009; Nassar & Lev‐Yadun, 2009; Ronel & Lev‐Yadun, 2009; Ronel et al ., 2009, 2010), we characterized the thorn/spine/prickle system in the whole native wild flora of Israel. To the best of our knowledge, a whole‐flora approach of this character (defence by sharp appendages) has never been carried out before.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the study on the evolution of plant protection by spines and thorns conducted in our group (e.g. Lev‐Yadun, 2001, 2003a, b, 2006, 2009a, b, c, 2011; Lev‐Yadun & Ne'eman, 2004, 2006; Halpern et al ., 2007a, b, 2011; Ronel, Malkiel & Lev‐Yadun, 2007; Lev‐Yadun & Gould, 2008; Lev‐Yadun & Halpern, 2008; Lev‐Yadun, Ne'eman & Izhaki, 2009; Nassar & Lev‐Yadun, 2009; Ronel & Lev‐Yadun, 2009; Ronel et al ., 2009, 2010), we characterized the thorn/spine/prickle system in the whole native wild flora of Israel. To the best of our knowledge, a whole‐flora approach of this character (defence by sharp appendages) has never been carried out before.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic colorful flowers, which were one of the first plant organs proposed to be aposematic [28,100], are, like almost all flowers, typically symmetric. Thus, Lev-Yadun [123] suggested that, as is the case in various animals, visual aposematism in spiny and poisonous plants also seems to be commonly associated with symmetry, including that of flowers and inflorescences. For instance, the flowering spiny inflorescences of many Near Eastern species of the Asteraceae (Figure 5), as well as those of other spiny taxa [55,113] (Figure 6), are radially symmetric.…”
Section: Flower Symmetry In Spiny and Toxic Plants And Aposematismmentioning
confidence: 98%
“…In nature, highly saturated colors are signals of danger or reward. For instance, poisonous creatures, like snakes and aposematic plants, often use their vivid, highly saturated colors as a warning to other creatures 21,22 . For some birds and reptiles, highly saturated body colors are a sign of aggression 23‐25 .…”
Section: Prior Literature and Conceptual Frameworkmentioning
confidence: 99%